Antagonistic Nodule Endophytic Bacteria Effective Against (Sclerotium rolfsii) Causing Stem Rot Disease in Groundnut - , Meghana Deva; , Ramya Vittal; , S. Ameer Basha; , S. N. C. V. L Pushpavalli; , Vidyasagar, B (Archives of Current Research International, 2024)
Groundnut is a major oilseed crop grown throughout the world. The crop is constrained by several biotic and abiotic stresses, among which stem rot disease caused by Sclerotium rolfsii poses significant threat to groundnut production. The management of stem rot disease using chemical methods has adverse health and ecological impacts. Eco-friendly alternatives such as the use of microbial antagonists including bacterial endophytes is an sustainable approach. In this context, the study explored the potential of nodule endophytic bacteria of groundnut for antagonism against S. rolfsii. A survey was conducted in major groundnut growing regions of Telangana during rabi, 2023. Eight different isolates of S. rolfsii and twenty nodule endophytic bacterial isolates were isolated from the infected and healthy groundnut plants, respectively. S. rolfsii isolate GNS1 was the most virulent of all with the lowest incubation period and days to permanent wilting. Among the 20 bacterial endophytes, isolates GNEB13 and GNEB6 were the most effective with highest mycelial inhibition of S. rolfsii under in vitro conditions. These isolates have the potential to be evaluated under field conditions for sustainable management of stem rot disease in groundnut.